Phytochemical And Bioactivity Studies Of Mimusops Elengi L - Amir, Faheem (2011)
Phytochemical investigation of the chloroform extracts of the leaves and bark of Mimusops elengi led to the isolation of spinasterol [15], ursolic acid [18] and 3β,6β,19α,23-tetrahydroxyurs-12-en-28-oic acid [67] from the leaves, as well as taraxerol [16] and spinasterol 3-O-β-D-glucopyranoside [39] from the bark. Compound [15] has previously been reported from the bark and seeds, compound [18] has been reported from the bark and mesocarp, and compound [39] has been reported from seeds of the plant.